The Effect of Combination Catfish Nuggets and Omega-3 Eggs in Addressing Stunting in Toddlers - Sartika, Rini; Kusumastuti, Nurry Ayuningtyas; Winarni, Lastri Mei (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Stunting is still a scourge for Indonesia society, the incidence of which has not been reduce to date. Accelerating the reduction in stunting rates is still a priority for the Indonesian government in order to immediately achieve the reduction according to the expected target. Good and healthy nutritional conditions during infancy (under five years of age) are an important foundation for their health and well-being in the future. This study aimed to determine the effect of combination of catfish nuggets and omega-3 eggs in overcoming stunting in toddlers. Subjects and Method: Method of this study used true experimental with a two group pretest post-test control group design. The total samples of 30 toddlers was divided into 2 groups of 15 respondents each group, it was the intervention group which was given combination of catfish nuggets and Omega-3 Eggs and the control group which was not given it during 2 weeks. Technique sampling was cluster random sampling. The instrument used lenghtboard for height and observation form for combination of catfish nuggets and Omega-3 Eggs. Data analysis used Wilcoxon test. Results: The mean of height for toddlers increased after given combination of catfish nuggets and Omega-3 Eggs (Mean =-2.17; SD= 0.97) compared to before intervention (Mean= -2.52; SD= 0.87), and the results were statistically significant (p<0.001) Conclusion: Combination of catfish nuggets and Omega-3 Eggs effective is increase the height for toddlers.